1998
DOI: 10.1007/bf02458357
|View full text |Cite
|
Sign up to set email alerts
|

Research fronts in library and information science in Spain (1985–1994)

Abstract: Publications and author cocitations in library and information science in Spain during the period from 1985 to 1994 were analyzed as a measure of the structure, specificity and composition of research fronts in this country. A cocitation matrix developed from an ad hoc database was subjected to cluster analysis, multidimensional scaling and principal components analysis, The resulting cocitation maps identified specific areas of r~search and their knowledge bases. We inferred the degree of consolidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…We described them in a previous study [13] Among the methodologies of a connectionist nature, the artificial neural networks (ANN) are now the most widely used, in particular the model called the self-organizing map (SOM, also known as the Kohonen model). It is based on the principle of the self-organization and grouping of n-dimensional vectors in a bidimensional space [14], and has been used to reduce dimensions in a wide variety of document spaces of diverse nature [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We described them in a previous study [13] Among the methodologies of a connectionist nature, the artificial neural networks (ANN) are now the most widely used, in particular the model called the self-organizing map (SOM, also known as the Kohonen model). It is based on the principle of the self-organization and grouping of n-dimensional vectors in a bidimensional space [14], and has been used to reduce dimensions in a wide variety of document spaces of diverse nature [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the disciplinary domain studies in which one of the main difficulties reported resides in the selection of the entities (authors, journals, etc.) to include in the analysis [6,14,26], in institutional domains these entities are indeed given. For institutions with a multidisciplinary profile, the difficulties lie both in determining the boundaries between subject groupings that arise in the disciplinary structure, and in establishing the cutoff point for citation and cocitation frequency in order to guarantee the validity of the representations obtained.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the aforementioned papers substantiate academicpractitioner separation in Spain, in particular the study on research fronts through co-citation analysis by Moya-Anegón et al (1998), which identifies the practitioner community as a clearly segregated cluster with its own personality. Despite the passage of time, data collected in the cited works continue to be reflected in the current trend, a phenomenon the present study sets out to demonstrate.…”
Section: Journal Of Informationmentioning
confidence: 99%